Predictive value of routine point-of-care cardiac troponin T measurement for prehospital diagnosis and risk-stratification in patients with suspected acute myocardial infarction. Issue 4 (June 2019) - Rasmussen, Martin B; Stengaard, Carsten; Sørensen, Jacob T; Riddervold, Ingunn S; Hansen, Troels M; Giebner, Matthias; Rasmussen, Claus-Henrik; Bøtker, Hans E; Terkelsen, Christian J
Objective: The purpose of this study was to determine the predictive value of routine prehospital point-of-care cardiac troponin T measurement for diagnosis and risk stratification of patients with suspected acute myocardial infarction. Methods and results: All prehospital emergency medical service vehicles in the Central Denmark Region were equipped with a point-of-care cardiac troponin T device (Roche Cobas h232) for routine use in all patients with a suspected acute myocardial infarction. During the study period, 1 June 2012–30 November 2015, prehospital point-of-care cardiac troponin T measurements were performed in a total of 19, 615 cases seen by the emergency medical service and 18, 712 point-of-care cardiac troponin T measurements in 15, 781 individuals were matched with an admission. A final diagnosis of acute myocardial infarction was confirmed in 2187 cases and a total of 2150 point-of-care cardiac troponin T measurements (11.0%) had a value ≥50 ng/l, including 966 with acute myocardial infarction (sensitivity: 44.2%, specificity: 92.8%). Patients presenting with a prehospital point-of-care cardiac troponin T value ≥50 ng/l had a one-year mortality of 24% compared with 4.8% in those with values <50 ng/l, log-rank: p <0.001. The following variables showed the strongest association with mortality in multivariable analysis: point-of-care cardiac troponin T≥50 ng/l (hazard ratio 2.10, 95% confidence interval: 1.90–2.33), congestive heart failure (hazard ratio 1.93, 95% confidence interval: 1.74–2.14), diabetes mellitus (hazard ratio 1.42, 95% confidence interval: 1.27–1.59) and age, one-year increase (hazard ratio 1.08, 95% confidence interval: 1.08–1.09). Conclusions: Patients with suspected acute myocardial infarction and a prehospital point-of-care cardiac troponin T ≥50 ng/l have a poor prognosis irrespective of the final diagnosis. Routine troponin measurement in the prehospital setting has a high predictive value and can be used to identify high-risk patients even before hospital arrival so that they may be re-routed directly for advanced care at an invasive centre.